The association of the Clock 3111 T/C SNP with lipids and lipoproteins including small dense low-density lipoprotein: results from the Mima study - Takahashi Kaoru; Fujiwara Shinji; Sano Yoshiko; Kotani Kazuhiko; Tsuzaki Kokoro; Sakane Naoki (BMC Medical Genetics, 2010)
Abstract Background The clock molecule plays major roles in circadian rhythmicity and regulating lipid and glucose metabolism in peripheral organs. Disruption of the circadian rhythm can lead to cardiometabolic disorders. The existence of small dense low-density lipoprotein (sdLDL) in the circulation, an abnormality of lipid metabolism, in part associated with lifestyle, is also one of risk parameters for cardiometabolic disorders. The 3111 T/C single nucleotide polymorphism (SNP) of the Clock gene has been reported to be associated with lifestyle including morning/evening preference. We investigated whether the Clock 3111 T/C SNP may affect lipids and lipoproteins including sdLDL. Methods In 365 community-dwelling subjects (170 men and 195 women, mean age 63 ± 14 years), the 3111 T/C SNP was genotyped using a fluorescent allele-specific DNA primer assay system. The levels of sdLDL were measured with the electrophoretic separation of lipoproteins employing the Lipoprint system. Results The frequency of the Clock 3111 C allele was 0.14. The area of sdLDL did not differ between the subjects with obesity and those without. In carriers of T/T homozygotes, the area of sdLDL was significantly higher compared with carriers of the C allele (T/C or C/C) (1.7 ± 3.4 vs. 0.8 ± 1.9%; p < 0.05). A multiple regression analysis showed that the area of sdLDL was significantly and negatively correlated with the Clock 3111 T/C SNP (β = -0.114, p < 0.05), independently of age, sex, body mass index, and exercise habits. Conclusion Our findings indicated that the Clock 3111 T/C SNP might be associated with the existence of sdLDL.